Retail Goods Brands’ Importance in Live Music Venue Preference - Tugba ORTEN TUGRUL (Communications of International Proceedings, 2021)
This study aims to determine the perceived importance of retail goods brands on live music venue selection, define distinctive customer segments to whom retail branding is important at different levels, and explore whether these segments differ by demographical characteristics. Data was collected from 424 participants through an online survey by using convenience sampling technique. Results revealed that customers perceive foods and alcoholic beverages brands to be important in selecting live music venue, whereas do not value branding attribute of tobacco products. In addition, three clusters of customers were found by using the perceived importance of retail goods brands: cross-category brand seekers, low interests, and category-specific brand seekers. This study argues that although retail goods planning and management is one of the neglected aspects of live music events, it is, in fact, a critical determinant in consumer preferences.
Keywords: Live Performance; Music; Branding; Retail; Venue; Consumer Preference.